ANALISIS IMPLEMENTASI PENGAWASAN EKSPOR IMPOR BARANG PADA KPPBC TIPE MADYA PABEAN JUANDA - Hidayat, Kadarisman; Setyawan, Arief; Herlinawati, Yunita (Jurnal Mahasiswa Perpajakan, 2016)
Indonesia one of the countries do export, import activities. In exporting / importing goods activity required controling. Institution that possesses of this is KPPBC Tipe Madya Pabean Juanda. The kind of research is descriptive qualitative approach. The result of this research shows implementation of controls export import of goods on KPPBC Tipe Madya Pabean Juanda are compliance with laws and customs regulations. Factors inhibiting the implementation of export controls of imported goods is an imbalance in the workload to be borne by the officer carrying out surveillance in the field, Factors inhibiting the implementation of controls export import of goods coming from service users (exporters,importers, PPJK) is if there are exporters or PPJK are still new and do not understand about customs procedures and is the uncertainty regarding the specifications listed in the customs documents. Factors supporting the implementation of export controls of imported goods originating from KPPBC Tipe Madya Pabean Juanda is conducive working environment, adequate infrastructure, and this agreement by KPPBC Tipe Madya Pabean Juanda while factors supporting the implementation of export import goods control from community is the lack of information related to indications of violations of customs of society. Keywords : Controling, Export , Import ABSTRAK Indonesia salah satu negara yang melakukan kegiatan ekspor impor barang. Dalam setiap kegiatan ekspor impor barang diperlukan pengawasan. Institusi yang memiliki tugas tersebut salah satunya adalah KPPBC Tipe Madya Pabean Juanda. Jenis penelitian yang dilakukan penelitian deskriptif pendekatan kualitatif. Hasil penelitian ini memperlihatkan implementasi pengawasan ekspor impor Ubarang pada KPPBC Tipe Madya Pabean Juanda sesuai dengan peraturan perundang- undangan kepabeanan. Faktor penghambat yang berasal dari KPPBC Tipe Madya Pabean Juanda adalah kurang seimbangnya jumlah beban kerja yang harus ditanggung oleh petugas yang melakukan pengawasan di lapangan, faktor penghambat yang berasal dari pengguna jasa adalah adanya eksportir baru yang belum memahami peraturan tentang ekspor dan ketidakjelasan spesifikasi yang dicantumkan dalam dokumen pelengkap pabean. Faktor pendukung yang berasal dari KPPBC Tipe Madya Pabean Juanda adalah lingkungan kerja yang kondusif, sarana dan prasarana yang memadai, dan kerjasama yang dijalin sedangkan faktor pendukung yang berasal dari masyarakat adalah adanya informasi terkait indikasi terjadinya pelanggaran kepabeanan dari masyarakat. Kata Kunci : Pengawasan, Ekspor , Impor